2017
DOI: 10.1103/physreve.96.062605
|View full text |Cite
|
Sign up to set email alerts
|

Clogging of soft particles in two-dimensional hoppers

Abstract: Using experiments and simulations, we study the flow of soft particles through quasi-twodimensional hoppers. The first experiment uses oil-in-water emulsion droplets in a thin sample chamber. Due to surfactants coating the droplets, they easily slide past each other, approximating soft frictionless disks. For these droplets, clogging at the hopper exit requires a narrow hopper opening only slightly larger than the droplet diameter. The second experiments use soft hydrogel particles in a thin sample chamber, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 49 publications
3
74
0
Order By: Relevance
“…For a large variety of hard, frictional spherical grains, it has been shown that the diameter of the opening must be larger than approximately five times the particle diameter to avoid clogs [1,2]. When the particles are soft and slippery, they flow through much narrower outlets without clogging [3][4][5]. For non-spherical particles, shape parameters influence the discharge statistics [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a large variety of hard, frictional spherical grains, it has been shown that the diameter of the opening must be larger than approximately five times the particle diameter to avoid clogs [1,2]. When the particles are soft and slippery, they flow through much narrower outlets without clogging [3][4][5]. For non-spherical particles, shape parameters influence the discharge statistics [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…with the determination of flow rates [1,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], the statistics of clogging [2,[23][24][25][26][27][28][29][30], the influences of obstacles near the orifice on the flow rates [31,32], and the role of gravity and embedding fluids [33][34][35]. The role of softness has been considered only recently in a few papers [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Pedestrian systems are probably the most dramatic example of clogging, but this phenomenon is rather general for systems composed of many discrete particles that flow through constrictions. Indeed, this topic has been the focus of research in a variety of fields such as microbial populations [8], colloids [9], droplets [10], granular matter [11] or robots [12]. Recently a phase diagram has been proposed to encompass clogging in such many different systems [13].…”
Section: Introductionmentioning
confidence: 99%
“…Soft particle packings, which yield hard particle systems in the limit of zero overlap, have also been the subject of considerable interest [32,33,34,35]. Recently such packings of soft frictionless particles have also been realized experimentally [36,37,38,39].…”
mentioning
confidence: 99%